Gender specific profiles of white coat and masked hypertension impacts on arterial structure and function in the SardiNIA study. (15th August 2016) - Scuteri, Angelo; Morrell, Christopher H.; Orru', Marco; AlGhatrif, Majid; Saba, Pier Sergio; Terracciano, Antonio; Ferreli, Liana Anna Pina; Loi, Francesco; Marongiu, Michele; Pilia, Maria Grazia; Delitala, Alessandro; Tarasov, Kirill V.; et al.
Abstract: Background: There is no definite consensus on the CV burden associated to Masked hypertension (MH) or White Coat Hypertension (WCH) — conditions that can be detected by out-of-office blood pressure measurements (24 hour Ambulatory Blood Pressure Monitoring, 24 h ABPM). Methods: We investigated the association of WCH and MH with arterial aging, indexed by a range of parameters of large artery structure and function in 2962 subjects, taking no antihypertensive medications, who are participating in a large community-based population of both men and women over a broad age range (14–102 years). Results: The overall prevalence of WCH was 9.5% and was 5.0% for MH, with 54.9% of subjects classified as true normotensive and 30.6% as true hypertensive. Both WCH and MH were associated with a stiffer aorta, a less distensible and thicker common carotid artery, and greater central BP than true normotensive subjects. Notably, the profile of arterial alterations in WCH and MH did not significantly differ from what was observed in true hypertensive subjects. The arterial changes accompanying WCH and MH differed in men and women, with women showing a greater tendency towards concentric remodeling, greater parietal wall stress, and PWV than men. Conclusion: Both WCH, and MH are associated with early arterial aging, and therefore, neither can be regarded as innocent conditions. Future studies are required to establish whether measurement of arterial aging parameters in subjects with WCH or MH will identify subjects at higher risk of CV events and cognitive impairment, who may require more clinical attention and pharmacological intervention. Highlights: MH also is accompanied by alteration in arterial properties. The arterial impact of WCH and MH is similar to what observable in true HT. The arterial impact of MH differs in a gender-specific manner. Both WCH and MH are not innocent conditions: they are associated with early arterial aging. Routine measurement of arterial properties in subjects with WCH or MH may identify subjects at higher risk of CV events.